May I have your attention, please? - Hilicki, Chris (John Wiley & Sons, Inc., 2005)
It will provide you with the knowledge and support you need to: Unlock your individual or corporate identity as you acknowledge and appreciate the true stories, experiences, and formative events in your personal or professional life that will set the foundation for your future success; Use the insights gained to determine what is important to you, and what defines your values and beliefs; Translate those values into a look, sound, and feel that is your unique identity—your authentic brand—and leverage that brand for personal and professional success